Identifying predictors of drug court graduation: findings from an evaluation of the Milwaukee County Adult Drug Treatment Court - Sheeran, Alyssa (Criminal justice studies, 2022)
Adult drug treatment courts provide an alternative to incarceration that focuses on the treatment of substance abuse issues and other psychological dysfunctions. The literature thus far has generally indicated that drug courts are significantly more effective than other criminal justice interventions, yet rates of drug court effectiveness vary substantially across jurisdictions. The current study was able to peek inside the “black box” of drug treatment courts to understand which characteristics might be critical to the success of these courts. An evaluation of the Milwaukee County Adult Drug Treatment Court in Wisconsin revealed that age at intake, race and ethnicity, prior convictions, primary drug of choice, and custody sanctions were all significantly associated with an individual’s likelihood of graduating the drug court. The inclusion of these findings to the literature offers an additional examination of drug court effectiveness and further assists in providing a more comprehensive understanding of the factors that predict drug court graduation. As a result, the health of the individual, the community, and the justice system at large can be significantly improved.